If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + -3x = -24 + -6x Solving -12 + -3x = -24 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -12 + -3x + 6x = -24 + -6x + 6x Combine like terms: -3x + 6x = 3x -12 + 3x = -24 + -6x + 6x Combine like terms: -6x + 6x = 0 -12 + 3x = -24 + 0 -12 + 3x = -24 Add '12' to each side of the equation. -12 + 12 + 3x = -24 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = -24 + 12 3x = -24 + 12 Combine like terms: -24 + 12 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 2(y+4)=18 | | 6u-12u= | | -5(n+3)-7+8n= | | j/3=2/5 | | -5(z+3)+4(3z-4)=6(z-3)+14 | | 6(3-2x)=1-(2x-1) | | 4-7+8=4(n)+4(n) | | -2x+9=-3x+29 | | 7x-16=6x-12 | | Z=5+2i | | -4(x-2)=4(2x+5) | | -log*(x)=0.85 | | 20x+25=19x+29 | | a(1+2a)-a(4a-5)= | | 25x^4=61x^2-36 | | 12(h-1)=6h+4+2 | | -2m+0=180(-49y) | | 198=x+2*x*2 | | 14+5(2x+2)=-5 | | 8+3x+4=10 | | 198=x+2+x+2 | | 7-2n-n=-14 | | 12/42=4w/56 | | -2+0=180(-49y) | | w=3ab | | x/8.9=22 | | 2z+8=4z-4 | | 4(2x-5)=-2(7-3x) | | -150h=400 | | 4x-1=2x-1+x+2 | | 198=l*w*h | | 4x-50=3x+50 |